C-terminal domain of ICA69 interacts with PICK1 and acts on trafficking of PICK1-PKCα complex and cerebellar plasticity. - Zhen Wang (Public Library of Science (PLoS), 2013)
Background PICK1 (protein interacting with C-kinase 1) is a PKC (protein kinase C)-binding protein, which is essential for synaptic plasticity. The trafficking of PKCα-PICK1 complex to plasma membrane is critical for the internalization of GluR2 and induction of long-term depression. ICA69 (islet cell autoantigen 69 kDa) is identified as a major binding partner of PICK1. While heteromeric BAR domain complex is suggested to underlie the interaction between PICK1 and ICA69, the role of C-terminal domain of ICA69 (ICAC) in PICK1-ICA69 complex is unknown. Methodology/principal findings We found that ICAC interacted with PICK1 and regulated the trafficking of PICK1-PKCα complex. ICAC and ΔICAC (containing BAR domain) might function distinctly in the association of ICA69 with PICK1. While ΔICAC domain inclined to form clusters, the distribution of ICAC was diffuse. The trafficking of PICK1 to plasma membrane mediated by activated PKCα was inhibited by ICA69. This action might ascribe to ICAC, because overexpression of ICAC, but not ΔICAC, interrupted PKCα-mediated PICK1 trafficking. Notably, infusion of maltose binding protein (MBP) fusion protein, MBP-ICA69 or MBP-ICAC, in cerebellar Purkinje cells significantly inhibited the induction of long-term depression at parallel fiber- and climbing fiber-Purkinje cell synapses. Conclusions Our experiments showed that ICAC is an important domain for the ICA69-PICK1 interaction and plays essential roles in PICK1-mediated neuronal plasticity.